2019
DOI: 10.1590/2175-8239-jbn-2018-0186
|View full text |Cite
|
Sign up to set email alerts
|

High grade renal trauma due to blunt injury in children: do all require intervention?

Abstract: Introduction: The aim of this study was to analyze the presentation and management of major grade renal trauma in children. Method: A retrospective study was performed including data collected from the patients who were admitted in Pediatric surgery with major grade renal injury (grade 3 and more) from January 2015 to August 2018. Demography, clinical parameters, management, duration of hospital stay and final outcome were noted. Results: Out of 13 children (9 males and 4 females), with age range 2-12 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
2
3
0
1
Order By: Relevance
“…The most prominent clinical features of kidney trauma patients are ank pain and gross hematuria [1,7,11,15]. Our study also found similar results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most prominent clinical features of kidney trauma patients are ank pain and gross hematuria [1,7,11,15]. Our study also found similar results.…”
Section: Discussionsupporting
confidence: 87%
“…Blunt renal injuries in children are seldom isolated, and multiorgan injury (liver, spleen, closed head, orthopedic fractures) is the general rule [4]. Several associated organ injuries that are commonly found in traumatic kidney injury are spleen and liver [15]. This condition can occur due to the organs' proximity to the kidney.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Several associated organ injuries that are commonly found in traumatic kidney injury are spleen and liver. 25 This condition can occur due to the organs’ proximity to the kidney. The other injuries found in our study were traumatic brain injury, bone fracture, associated abdominal trauma injury, and burn injury.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other identified risk factors, isolated BRT is rarer and often presumed a more minor injury, 14,15 leading potentially to less timely evaluation. Nonetheless, case reports of severe isolated kidney injuries have been reported, 16 as well as retrospective studies suggesting isolated renal injuries are more common in younger children 17 .…”
Section: Discussionmentioning
confidence: 99%